A new approach to obtain cellulose nanocrystals and ethanol from eucalyptus cellulose pulp via the biochemical pathway. (14th May 2017) - Bondancia, Thalita J.; Mattoso, Luiz Henrique C.; Marconcini, José M.; Farinas, Cristiane S.
Abstract : The feasibility of integration of cellulosic ethanol production with the manufacture of cellulose nanofibers (CNF) and cellulose nanocrystals (CNC) was evaluated using eucalyptus cellulose pulp as feedstock and employing the biochemical route alone. For the enzymatic hydrolysis step, experimental central composite design (CCD) methodology was used as a tool to evaluate the effects of solids loading (SL) and enzymatic loading (EL) on glucose release and cellulose conversion. Glucose concentrations from 45 to 125 g/L were obtained after 24 h, with cellulose conversions from 35 to 96%. Validation of the statistical model was performed at SL of 20% and EL of 10 mg protein/g, which was defined by the desirability function as the optimum condition. The sugars released were used for the production of ethanol by Saccharomyces cerevisiae, resulting in 62.1 g/L ethanol after 8 h (yield of 95.5%). For all the CCD experimental conditions, the residual solids presented CNF characteristics. Moreover, the use of a new strategy with temperature reduction from 50 to 35°C after 24 h of enzymatic hydrolysis enabled CNC to be obtained after 144 h. The CNC showed a crystallinity index of 83%, length of 260 nm, diameter of 15 nm, and aspect ratio (L/D) of 15. These characteristics are suitable for many applications, such as reinforcement in polymeric materials and other lower volume higher value bio‐based products. The findings indicate the viability of obtaining ethanol and CNC using the biochemical route exclusively, potentially contributing to the future implementation of forest biorefineries. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1085–1095, 2017